2017
DOI: 10.1111/add.13840
|View full text |Cite
|
Sign up to set email alerts
|

Prescription contraception use and adherence by women with substance use disorders

Abstract: Women with substance use disorders are less likely to use prescription contraceptives, especially long-acting methods, but are not significantly less likely to adhere to them once prescribed than women without substance use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This includes concerns and lack of knowledge about side effects, overestimation of efficacy of all forms of Tier 2 and Tier 3 methods, and overreliance on verbal testimonies of other women’s experiences with LARC methods [ 32 34 ]. Substance abusing women have been demonstrated to hold additional perceptions that may impact LARC preferences including: misperception of fertility; underestimation of the benefits of LARC; overestimation of the costs and risks associated with LARC; intimate partner violence; fear of losing custody of children; and denial or embarrassment of their substance use [ 21 23 ]. Understanding the factors that may make women hesitant about LARC methods relative to injections is important because injections have not been demonstrated to have high rates of use among drug-using women [ 25 ] and at least one study has demonstrated reduced injection adherence among an opioid using sample [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes concerns and lack of knowledge about side effects, overestimation of efficacy of all forms of Tier 2 and Tier 3 methods, and overreliance on verbal testimonies of other women’s experiences with LARC methods [ 32 34 ]. Substance abusing women have been demonstrated to hold additional perceptions that may impact LARC preferences including: misperception of fertility; underestimation of the benefits of LARC; overestimation of the costs and risks associated with LARC; intimate partner violence; fear of losing custody of children; and denial or embarrassment of their substance use [ 21 23 ]. Understanding the factors that may make women hesitant about LARC methods relative to injections is important because injections have not been demonstrated to have high rates of use among drug-using women [ 25 ] and at least one study has demonstrated reduced injection adherence among an opioid using sample [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…By improving contraception adherence, it is possible LARC methods also reduce the likelihood of unintended pregnancy among opioid using populations. However, while these products are safe and effective [ 20 ], there may be a gap in patient knowledge about LARC methods and/or patient and provider barriers to accessing LARC methods that may limit use among women in this population [ 21 23 ]. Most fundamentally, it is not known what women who use opioids think about these contraception options.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research demonstrated that women with SUD use prescription contraception less often than women without SUD, especially long-acting reversible contraception (Terplan et al, 2015). However, women with SUD are open to receiving family planning services in conjunction with substance use treatment (Robinowitz et al, 2016) and will demonstrate similar adherence to prescription contraceptives as women without SUD once prescribed (Griffith et al, 2017). Periconceptional and early pregnancy periods also offer unique opportunities to conduct screening and brief intervention to minimize the risk of FASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent retrospective analysis of claims and encounter data for women 16–45 years found no significant association between substance use disorder and contraceptive adherence regardless of contraceptive method selected. 23…”
Section: Discussionmentioning
confidence: 99%